Identification of a Potent and Selective GPR4 Antagonist as a Drug Lead for the Treatment of Myocardial Infarction - Fukuda, Hayato (ACS Med Chem Lett, 2016)
[Image: see text] GPR4, a pH-sensing G protein-coupled receptor, is highly expressed in endothelial cells and may be activated in myocardial infarction due the decreased tissue pH. We are interested in GPR4 antagonists as potential effective pharmacologic tools and/or drug leads for the treatment of myocardial infarction. We investigated the structure–activity relationship of a known GPR4 antagonist 1 as a lead compound to identify 3b as the first potent and selective GPR4 antagonist, whose effectiveness was demonstrated in a mouse myocardial infarction model.